1980
DOI: 10.1677/joe.0.0840231
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of the Suprachiasmatic Nuclei and the Serotonin-Dependent Phasic Release of Luteinizing Hormone in the Rat: Effects on Drinking Rhythmicity and on the Consequences of Preoptic Area Stimulation

Abstract: Ovariectomized rats in which less than 7% of the suprachiasmatic nuclei had been spared by bilateral radiofrequency lesions were distinguishable from those with greater than 40% of the nuclei by their consistent failure to show the oestrogen-induced daily surge of LH, either with or without pharmacological manipulations of serotonin (5-HT), and also by their loss of the normal rhythmicity of drinking. Minor damage to structures adjacent to the suprachiasmatic nuclei was similar in both groups. The identical fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…This finding was confirmed in another report that also found a disruption of the ACTH rhythm by SCN lesions [73]. It was reported that lesions of the SCN of ovariectomized female rats abolished the estrogen-induced LH surge as well as disrupting the rhythmicity of drinking behavior [74]. In squirrel monkeys, SCN lesions resulted in the abolition of circadian drinking behavior [75]; however, this process took several weeks, suggesting the existence of other circadian components outside the SCN in this primate.…”
Section: Evidence For the Scn As The Circadian Pacemakersupporting
confidence: 80%
See 1 more Smart Citation
“…This finding was confirmed in another report that also found a disruption of the ACTH rhythm by SCN lesions [73]. It was reported that lesions of the SCN of ovariectomized female rats abolished the estrogen-induced LH surge as well as disrupting the rhythmicity of drinking behavior [74]. In squirrel monkeys, SCN lesions resulted in the abolition of circadian drinking behavior [75]; however, this process took several weeks, suggesting the existence of other circadian components outside the SCN in this primate.…”
Section: Evidence For the Scn As The Circadian Pacemakersupporting
confidence: 80%
“…The literature on TSH release both in young and elderly humans is somewhat limited and controversial, with reports of increased [15] or unchanged [16] levels during aging. In the most convincing study comparing young (20-27 year) and elderly (67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84) year) men in a circadian context, it was found that in young humans, TSH release has a circadian rhythmicity, with increases observed beginning at night (#22:00 h), approximately 3-4 h before sleep onset, levels remaining elevated at night and then decreasing during the morning ( fig. 2) [17].…”
Section: Thyroid-stimulating Hormonementioning
confidence: 99%
“…The SCN is the center for the major 'biological clock', and its integrity is critical for maintenance of regular estrous cyclicity [36] as well as circa dian rhythmicity of other physiological functions [37,38[. In males, diurnal rhythms in cAMP concentrations occur in SCN which can be entrained to the photoperiod and are independent of corticosterone rhythm [39].…”
Section: Discussionmentioning
confidence: 99%
“…If these signals are delayed or suppressed sufficiently, preovulatory gonadotropin release is delayed by an entire day and occurs at the proper time 24 hr later. The suprachiasmatic nucleus (SCN) is often called the "biological clock" because its integrity is critical to the maintenance of biological functions that have a circadian basis, including cyclic reproductive function (8)(9)(10)(11)(12). Previous studies demonstrated that the diurnal rhythms of norepinephrine and serotonin turnover rates, which accompany cyclic luteinizing hormone (LH) release, are altered in the SCN of middle-aged rats when they enter the transition to age-related estrous acyclicity (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%